I Can See You: Temporal Variation in Ant Aggressiveness Towards Herbivores under Continuous Provision of High- or Low-quality Food Sources - Pena, J. C. C. [UNESP]; Luna, P.; Aoki-Goncalves, F.; Jacobo, M. F. C.; Patino, T. M.; Morales, K. S.; Vazquez, M. V.; Garcia-Chavez, J. H.; Dattilo, W. (Univ Estadual Feira Santana, 2020)
To reduce herbivory, plants bearing extrafloral nectaries interact with ants and attract them by providing food. As plant bodyguards, ants respond to the resource provision and, using their antennae, detect chemical messages from the host plants that help them to locate herbivores. Ants can also use their vision to explore the environment; however, information is lacking on how interactions between visual signs and the availability of extrafloral nectar affect ant aggressiveness near resources. We addressed the following question in this study: does the ants' ability to visualize potential herbivores enhance their aggression under a constant provision of a high-quality food source? Using an experimental approach within the semiarid intertropical region of Tehuacan-Cuicatlan (Mexico), we manipulated the availability of food sources by constantly offering artificial nectaries on the shrub Prosopis laevigata (Fabaceae). Over two time periods (day and night), we tested how the presence of a high-quality food source affected ant aggressiveness to herbivores. Therefore, we offered dummy caterpillars and counted the number of marks left by enemy attacks. Overall the attack rate was extremely high: 84.25% of the dummy caterpillars were injured. Ants were responsible for 86.22% of the marks left by enemies, and their aggression increased during the day, especially towards caterpillars in trees with high-quality food sources. During the night, ants probably rely mostly on their antennae to detect potential herbivores; therefore, their ability to detect dummy caterpillars was greater during the day. We show that, besides nectar quality and availability, visualizing herbivores may enhance ant aggressiveness.
Keywords: Ant-plant-herbivore interactions; artificial nectaries; semiarid environments; dummy caterpillars; multitrophic interactions; enemy free space